Role of Liquid–Liquid Phase Separation in Assembly of Elastin and Other Extracellular Matrix Proteins. Issue 23 (2nd November 2018) - Muiznieks, Lisa D.; Sharpe, Simon; Pomès, Régis; Keeley, Fred W.
Abstract: Liquid–liquid phase separation resulting in formation of colloidal droplets has recently attracted attention as a mechanism for rapid and transient assembly of intracellular macromolecules into functional units. Phase separation also appears to be a widespread and evolutionarily ancient mechanism for organization of proteins of the extracellular matrix into fibrillar, polymeric assemblies. Elastin, which provides the physical properties of extensibility and elastic recoil to large arteries, lungs and other tissues, is the best-characterized extracellular matrix protein whose polymeric assembly is initiated by phase separation. Recent studies have provided an atomistic description of the conformational ensemble of elastin-like proteins, and have begun to uncover how the interplay of local secondary structure, hydrophobicity and conformational disorder govern the structure, assembly and function of elastin. Monomeric elastin is a non-polar, glycine-rich, low-complexity, modular protein that remains predominantly disordered even in the crosslinked polymeric state, consistent with its function as an entropic elastomer. Unlike intracellular phase separation, which is reversible, phase separation of elastin and other matrix proteins proceeds to stabilization and clustering of condensed phase droplets and subsequent molecular organization into fibrillar, supramolecular structures. Short β-sheets appear to mediate the interaction and organization of these phase-separated droplets and modulate the ultimate material properties of the matrix. Whether phase separation is intracellular or extracellular, reversible or network-forming, understanding the sequence determinants of such varied assembly behaviors and differential fates of the colloidal droplets will provide important insights into aberrant assembly with pathological consequences and elucidate fundamental principles for the rational design of biomimetic materials. Graphical abstract: Highlights: Liquid–liquid phase separation is an important initial step in the assembly of many fibrillar extracellular matrix proteins, including elastin, resilin, abductin, spider silks proteins, insect cuticle and eggshell membrane proteins, mussel attachment proteins, aquatic adhesive proteins and others. All of these proteins are modular with low-complexity, proline-rich and/or glycine-rich sequences, and have been either shown or predicted to contain substantial regions of intrinsic disorder. Formation of condensed phase colloidal droplets of such matrix proteins is generally not reversible, with stabilization and clustering of droplets proceeding spontaneously to network formation. Varied assembly properties, differential fates of the condensed phase droplets and ultimate physical properties of the polymeric networks are determined by sequence characteristics of the proteins.